Detrimental effects of non-functional spermatozoa on the freezability of functional spermatozoa from boar ejaculate. - Maria J Martinez-Alborcia (Public Library of Science (PLoS), 2012)
In the present study, the impact of non-functional spermatozoa on the cryopreservation success of functional boar spermatozoa was evaluated. Fifteen sperm-rich ejaculate fractions collected from five fertile boars were frozen with different proportions of induced non-functional sperm (0--native semen sample-, 25, 50 and 75% non-functional spermatozoa). After thawing, the recovery of motile and viable spermatozoa was assessed, and the functional of the spermatozoa was evaluated from plasma membrane fluidity and intracellular reactive oxygen species (ROS) generation upon exposure to capacitation conditions. In addition, the lipid peroxidation of the plasma membrane was assessed by the indirect measurement of malondialdehyde (MDA) generation. The normalized (with respect to a native semen sample) sperm motility (assessed by CASA) and viability (cytometrically assessed after staining with Hoechst 33342, propidium iodide and fluorescein-conjugated peanut agglutinin) decreased (p<0.01) as the proportion of functional spermatozoa in the semen samples before freezing decreased, irrespective of the semen donor. However, the magnitude of the effect differed (p<0.01) among boars. Moreover, semen samples with the largest non-functional sperm subpopulation before freezing showed the highest (p<0.01) levels of MDA after thawing. The thawed viable spermatozoa of semen samples with a high proportion of non-functional spermatozoa before freezing were also functionally different from those of samples with a low proportion of non-functional spermatozoa. These differences consisted of higher (p<0.01) levels of intracellular ROS generation (assessed with 5-(and-6) chloromethyl-20,70-dichlorodihydrofluorescein diacetate acetyl ester; CM-H(2)DCFDA) and increased (p<0.01) membrane fluidity (assessed with Merocyanine 540). These findings indicate that non-functional spermatozoa in the semen samples before freezing negatively influence the freezability of functional spermatozoa.